Design and Investigation of RGB-type LED Visible Light Communication System - Sia , Jonathan Hong Tai; Chiak Kho, Melvin Chun; Hii, King Ung; Yong, Lisa (International Journal of Integrated Engineering, 2020)
This paper examines the feasibility of a Red Green Blue (RGB)-type Light Emitting Diode (LED) Visible Light Communication (VLC) system based on wavelength division multiplexing (WDM). Each color in the RGB-LED is individually modulated to increase the data rate by three times as compared to the single channel modulation approach used in conventional VLC system. Color filters are employed to detect separately the RGB signals at the receiver side. The proposed system utilized a reflector to improve the performance and the system is lens-free. In this work, an approach of approximated WDM testing is adopted due to the incapability of multiplexing by the microcontroller at higher data rate. The proposed system is demonstrated to transmit and receive data at a maximum distance of 1.4m, with total data transmission speed of 345.6 kbps using standard WDM, while a total speed of 1.5 Mbps up to maximum distance of 1.2m and 3 Mbps up to maximum distance of 0.7m is achieved by the approach of approximated WDM testing.